2021
DOI: 10.1088/1755-1315/940/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

The Waste Recycling of Sugarcane Bagasse-Based Biochar for Biogas Purification

Abstract: The utilization of the recycling of biomass waste for carbon dioxide (CO2) adsorption in biogas is still rare. Even though the experiments on the biogas purification still using synthetic biogas. This paper investigated the recycling of biomass waste, sugarcane bagasse for biogas purification. The conversion of biomass into biochar was claimed to expand the surface area of its pores for capturing CO2 in biogas. Five treatments of adsorbents used in this study, 100% volume of zeolite or biochar, 75% volume of z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The presence of CO 2 decreased the calorific value of biogas [114]. Wuri et al (2021) produced a biochar composite with natural zeolite that showed promising results for adsorbing CO 2 [115].…”
Section: Remediation Of Soil Pollutants and Gas Removalmentioning
confidence: 99%
“…The presence of CO 2 decreased the calorific value of biogas [114]. Wuri et al (2021) produced a biochar composite with natural zeolite that showed promising results for adsorbing CO 2 [115].…”
Section: Remediation Of Soil Pollutants and Gas Removalmentioning
confidence: 99%
“…An attempt to purify biogas was also made by Wuri et al 35 (Table 3). The sugarcane bagasse-derived biochar combined with natural zeolite was used to adsorb carbon dioxide from biogas.…”
Section: Biogas Purificationmentioning
confidence: 99%
“…8). The mixture of 50% naturally occurring zeolite and 50% sugarcane bagasse-based biochar exhibited the most favorable CO 2 reduction [129].…”
Section: Sugarcane Bagasse-based Biochar In Co 2 Adsorptionmentioning
confidence: 99%
“…Incorporating biochar into cementitious materials can provide Fig. 8 Purification of biogas using natural zeolites and bagasse biochar using in different ratios [129]. (According to the information presented in Fig.…”
Section: Sugarcane Bagasse-based Biochar In Building Constructionmentioning
confidence: 99%